Evaluation of a community pharmacy delivered oral contraception service. Issue 2 (25th August 2012) - Parsons, Judith; Adams, Christine; Aziz, Najia; Holmes, Jo; Jawad, Ruhi; Whittlesea, Cate
Abstract : Introduction: In the UK half of all pregnancies are unplanned and half of teenage pregnancies terminated. Southwark and Lambeth have the highest teenage conception rates in London. In 2009, many teenage pregnancies in Southwark led to terminations. A contraception service was established where qualified pharmacists supplied oral contraception (OC) using a patient group direction (PGD). This service evaluation aimed to assess this service delivered in five community pharmacies. Methods: Monthly data were submitted by each pharmacy to the Primary Care Trust on consultations, pills supplied, initial or subsequent supply and client referral. For specified periods consultation time was collected and a clinical notes audit undertaken. Client satisfaction was determined using a structured questionnaire returned to the pharmacy. Mystery shoppers were employed to assess the service. Results: A total of 741 consultations were undertaken by seven pharmacists at five community pharmacies (October 2009–June 2011) with many (45.5%) occurring following emergency contraception supply. The mean consultation time was 19 minutes . Combined OC was most commonly supplied with nearly half (46.1%) of initial supplies to first-time pill users. Most consultations (92.2%) were with women aged under 30 years, with 22.5% aged under 20. Most consultations were with black or black British clients. Of the 99 women who completed the satisfaction questionnaires, most clients were very satisfied or satisfied with the service and felt comfortable talking to the pharmacist about contraception. Conclusions: Trained pharmacists were clinically competent and provided OC in community pharmacy according to a PGD. This service was accessed by the target population; young women using emergency hormonal contraception who had not previously used OC. Clients were largely very satisfied with the service.